Postparturient liver diseases of dairy cattle (Ketosis, fatty liver). I. Etiology and Pathogenesis - PANOUSIS (Ν. ΠΑΝΟΥΣΗΣ) Ν.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ) H. (Journal of the Hellenic Veterinary Medical Society, 2018)
Two of the commonest in practice postparturient liver diseases of dairy cows, ketosis and fatty liver, are discussed in this paper. It is not uncommon for both diseases to occur simultaneously, or each to act as a predisposing factor for the other. These diseases share a common etiology and pathogenesis, which are energy imbalance and disruption of normal carbohydrate metabolism during the period of high milk yield. Poor herd management during the dry period and hormonal changes accompanying parturition, have been associated with fat utilization for energy production, which in turn leads to fatty infiltration of the liver and ketosis.